Act 919 of 2016 and its contribution to governance of the upstream petroleum industry in Ghana. Issue 1 (2nd January 2018) - Ndi, George
Abstract : In August 2016, the Ghanaian Parliament marked the advent of a new era for the country's nascent petroleum industry with the enactment into law of the Petroleum (Exploration and Production) Act ( Act 919 ) . Act 919 is considered to represent a major milestone in the legislative history of the upstream oil and gas industry in Ghana. The main objective of this article is to assess the new statute's fitness for purpose through a critical examination of its regulatory aspirations and its underlying legislative presumptions. The discussion is set against the historical background of petroleum exploration and production in Ghana.